Detection of Single Nanoparticles and Lentiviruses Using Microcavity Resonance Broadening. (12th August 2013) - Shao, Linbo; Jiang, Xue‐Feng; Yu, Xiao‐Chong; Li, Bei‐Bei; Clements, William R.; Vollmer, Frank; Wang, Wei; Xiao, Yun‐Feng; Gong, Qihuang
<x xml:space="preserve">Abstract</x> A new label‐free sensing mechanism is demonstrated experimentally by monitoring the whispering‐gallery mode broadening in microcavities. It is immune to both noise from the probe laser and environmental disturbances, and is able to remove the strict requirement for ultra‐high‐Q mode cavities for sensitive nanoparticle detection. This ability to sense nanoscale objects and biological analytes is particularly crucial for wide applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>